Etika Syariah dan Tekanan Kinerja dalam Praktik Akuntansi: Analisis Ketegangan antara Nilai Normatif dan Realitas Organisasional - Riandi saputra; Masyhuri Masyhuri (Journal of Economics, Management, and Accounting, 2026)
This study examines the tension between Sharia ethics and performance pressure in accounting practices by analyzing the gap between normative values and organizational realities. Sharia accounting is conceptually grounded in ethical principles that emphasize integrity, accountability, and social responsibility beyond financial performance. However, organizational demands such as performance targets, efficiency pressures, and competitive environments often challenge the consistent application of these values. Using a qualitative conceptual approach, this study analyzes ethical standards, accounting regulations, and prior empirical studies related to Islamic accounting practices. The findings indicate that performance-oriented organizational structures tend to marginalize ethical considerations, placing accountants in moral dilemmas that affect professional judgment and reporting quality. The study also finds that effective alignment between Sharia ethics and organizational practices requires institutional commitment, ethical leadership, integrated accounting standards, and continuous ethical education for accounting professionals. This research contributes to the development of Islamic accounting literature by highlighting the importance of systemic and cultural approaches in bridging ethical ideals with practical constraints, ensuring that Sharia-based accounting remains relevant, credible, and sustainable in modern organizational environments.